Design and simulation of a refractive index sensor based on SPR and LSPR using gold nanostructures - Armin Agharazy Dormeny; Parsoua Abedini Sohi; Mojtaba Kahrizi (Results in Physics, 2020)
A refractive index sensor to detect chemicals based on surface plasmon resonance is designed and analytically investigated by a finite element method via COMSOL multiphysics. A tunable sensitivity is achieved by patterning the continuous metallic thin films with cavities or protrusions. The simulation results exhibit that the improved sensitivity of the devices is attributed to the co-excitation of SPR and LSPR modes. This result is obtained by studying the variation of the electric field intensity along several cut lines through the metallic layer. The penetration depth of the plasmon field is characterized, and accordingly, SPR and LSPR modes of the sensors are determined. The proposed sensor is calibrated for eight substances with refractive indices ranging from 1.333 to 1.38. The linearity of the calibration curve indicates the applicability of the sensor to identify the refractive indices of unknown mediums as a function of resonance wavelength. This study is proposing a new way to show the duality nature of patterned thin films to support both propagating and localized surface plasmon modes.